IMMU-26. SAFETY AND EFFICACY OF PVSRIPO IN RECURRENT GLIOBLASTOMA: LONG-TERM FOLLOW-UP AND INITIAL MULTICENTER RESULTS. (12th November 2021) - Desjardins, Annick; Gromeier, Matthias; Friedman, Henry; Landi, Daniel; Friedman, Allan; Ashley, David M; Curry, William; Butowski, Nicholas; Sloan, Andrew; Wen, Patrick; Cavaliere, Robert; Gerstner, Elizabeth; et al.
Abstract: BACKGROUND: Recurrent glioblastoma (rGBM) is rapidly fatal (median overall survival [mOS] of ~9 months; OS at 12 months [OS12] < 35%) with approved therapies (lomustine±bevacizumab). PVSRIPO is an intratumoral immunotherapy targeting CD155 on antigen-presenting and malignant cells of solid tumors. Preclinically, PVSRIPO delivers a systemic, tumor antigen-specific, polyfunctional T-cell mediated anti-tumor response. Interim, single-center, phase (Ph) 1 results showed greater long-term survival with PVSRIPO vs. criteria-matched external control rGBM patients (Desjardins 2018). Updates to Ph1 safety (at the Ph2 dose) and efficacy and interim multicenter (Ph2) results are presented. METHODS: Adults with histologically-confirmed rGBM, Karnofsky performance status ≥ 70, and an active, supratentorial, contrast-enhancing lesion (1-5.5cm) received PVSRIPO (5x10 7 TCID50 ) intratumorally via convection-enhanced delivery on Day 1, with a planned follow-up of 24 months. Safety (treatment-emergent adverse events [TEAEs]), efficacy (reported as OS12, OS24, mOS), and blood/tissue were assessed. RESULTS: 149 patients (>90% with 1-2 prior progressions, including failure of SOC and patients with prior bevacizumab failure) received the Ph2 dose of PVSRIPO (n=30 received other doses in Ph1 with safety summarized previously). Follow-up durations for surviving patients were 51-74 months (Ph1) and 10-44 months (Ph2). No dose-limiting toxicities occurred; up to 97% of patients experienced mostly grade 1-2 related TEAEs; ≤ 23% patients experienced grade ≥ 3 related events. Neurologic symptoms related to peritumoral edema were most common ( > 90% patients) and were effectively managed with low-dose bevacizumab/corticosteroids. Survival estimates were: OS12: 54%, 50%; OS24: 18%, 17%; mOS: 12.3 (95% CI 10, 15.3), 12 (10.6, 13.7) months, for the Ph1 and Ph2 trials, respectively. Baseline correlates of longer survival included smaller lesions and methylated MGMT-promoter status. CONCLUSIONS: The multicenter/Ph2 study replicated the single-center/Ph1 results. Relative to published data with approved therapies, PVSRIPO was associated with greater long-term survival and mOS in patients with rGBM and was generally well-tolerated.